THE INFLUENCE OF AFFILIATE MARKETING AND USER REVIEWS ON PURCHASE DECISION’S FOR CHILDREN’S CLOTHING PRODUCTS AT GALERI AIKA STORE ON THE SHOPEE MARKETPLACE - Sindi Setiawati; Dadang Munandar (PT. Jurnal Center Indonesia Publisher, 2026)
The Aika Gallery store on the Shopee marketplace is the perfect destination for parents seeking children's clothing with guaranteed quality and attractive designs. The objectives of this study were (1) to determine affiliate marketing for children's clothing products at the Aika Gallery store on the Shopee marketplace, (2) to determine user reviews of children's clothing products at the Aika Gallery store on the Shopee marketplace, (3) to determine purchasing decisions for children's clothing products at the Aika Gallery store on the Shopee marketplace, (4) to determine the influence of affiliate marketing on purchasing decisions for children's clothing products at the Aika Gallery store on the Shopee marketplace, (5) to determine the influence of users on purchasing decisions for children's clothing products at the Aika Gallery store on the Shopee marketplace, and (6) to determine the simultaneous influence of affiliate marketing and user reviews on purchasing decisions for children's clothing products at the Aika Gallery store on the Shopee marketplace. This study used a descriptive quantitative approach with 70 respondents. The results of this study are: (1) Consumer responses regarding Affiliate Marketing are in the good category, (2) Consumer responses regarding User Reviews are in the good category, (3) Consumer responses regarding Purchasing Decisions are in the good category, (4) Affiliate Marketing has a significant influence on Purchase Decision Satisfaction (5) User Reviews have a significant influence on Purchase Decision Satisfaction, and (6) Affiliate Marketing and User Reviews have a significant influence on Purchase Decisions.